2022
DOI: 10.7150/thno.66464
|View full text |Cite
|
Sign up to set email alerts
|

Faecal microbiome and metabolic signatures in rectal neuroendocrine tumors

Abstract: Background: The prevalence of rectal neuroendocrine tumors (RNET) has increased substantially over the past decades. Little is known on mechanistic alteration in the pathogenesis of such disease. We postulate that perturbations of human gut microbiome-metabolome interface influentially affect the development of RNET. The study aims to characterize the composition and function of faecal microbiome and metabolites in RNET individuals. Methods: We performed deep shotgun metageno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…By studying stool samples from 18 patients with rectal neuroendocrine tumor (RNET) and 40 controls, Hu et al found that patients with RNET had aberrant depletion and attenuated connection. Finally, they suggest that this disordered ecological structure may contribute to the diseasecausing process of this tumor (110). In gastroenteropancreatic neuroendocrine tumors (GEP-NETs), the researchers found a significant decrease in bacterial species and an increase in fungi in the patients' gut microbes.…”
Section: Gut Microbes and Other Neuroendocrine Tumorsmentioning
confidence: 98%
“…By studying stool samples from 18 patients with rectal neuroendocrine tumor (RNET) and 40 controls, Hu et al found that patients with RNET had aberrant depletion and attenuated connection. Finally, they suggest that this disordered ecological structure may contribute to the diseasecausing process of this tumor (110). In gastroenteropancreatic neuroendocrine tumors (GEP-NETs), the researchers found a significant decrease in bacterial species and an increase in fungi in the patients' gut microbes.…”
Section: Gut Microbes and Other Neuroendocrine Tumorsmentioning
confidence: 98%
“…After extracting the DNA of all samples, the total DNA was immediately stored in dry ice, and metagenomic sequencing was performed as soon as possible. All samples were sequenced using the Illumina platform (insert size 300 bp, read length 125 bp) at Novogene Bioinformatics Technology Co., Ltd. [17] A paired-end library was constructed using NEXTFLEX Rapid DNA-Seq (Bioo Scienti c, Austin, TX, USA). Adapters containing the full complement of sequencing primer hybridization sites were ligated to the blunt end of the fragments.…”
Section: • Metagenomic Sequencing Gene Catalogue Construction and Met...mentioning
confidence: 99%
“…This shows the prevalence of microbial invasion in NENs. Hu et al profiled fecal samples for rectal NETs [ 99 ]. The results of that study are consistent with the general trend of the significant depletion of microbial species diversity in NETs.…”
Section: Microbial Communitymentioning
confidence: 99%
“…The results of that study are consistent with the general trend of the significant depletion of microbial species diversity in NETs. Bacteria, including Haemophilus parainfluenzae , Veillonella unclassified, and Streptococcus salivarius, were significantly enriched in the healthy group, while species such as Erysipelotrichaceae bacterium_6_1_45 , Varibaculum cambriense , and Methanobrevibacter smithii were abundant in the rectal NET group [ 99 ]. For the functional characterization of the microbiome, glycerophospholipid metabolism as a key tumor-specific pathway is distinctively aberrant in rectal NET patients and is positively correlated with Methanobrevibacter smithii , which is mainly due to changes in the proportion of microbial species [ 99 ].…”
Section: Microbial Communitymentioning
confidence: 99%
See 1 more Smart Citation